Edaphic and topographic characteristics associated with growth in volume of Gmelina arborea Roxb, in Tlatlaya, Mexico State - Telles Antonio, Ricardo; Alanís Rodríguez, Eduardo; Jiménez Pérez, Javier; Aguirre Calderón, Oscar Alberto; Treviño Garza, Eduardo Javier; de los Santos Posadas, Héctor Manuel (Instituto de Ecología, A.C., 2021)
Gmelina arborea is a fast-growing species easily adaptable to a diversity of site conditions; the objective of the study was to analyze the edaphic and topographic characteristics associated with the growth of G. arborea established in Mexico State and to develop a model to estimate the stem volume. The research was carried out in eight permanent sampling plots of circular shape (400 m2), where 5 soil subsamples were extracted from each plot, which were mixed to form a final sample of 500 grams. The analysis of edaphic characteristics was made based on NOM-021-RECNAT-2000 and data on altitude, slope, and depth. For the analysis of variance and test of means, a principal component analysis was carried out, followed by a multiple linear regression; the correlation coefficient was used to compare the correlations between the variables chosen with the R® statistical package. The resulting model took hydraulic conductivity, nitratesand the Ca/Mg ratio as predictor variables; this model explained 71.6% of the variability observed in the volume of the trunk (R2adjusted = 0.716). According to the variance results, these variables did not show significant differences. It is concluded that the variation of the edaphic and topographic characteristics influences the growth of the volume of the canopy. It is essential to know the autoecology of the species, which is associated with climatic and edaphological conditions, as well as altitudinal distribution.